2005
DOI: 10.1007/s00464-005-0184-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic radiofrequency ablation of hepatic cavernous hemangioma

Abstract: Laparoscopic RFA therapy is a safe, feasible, and effective treatment option for patients with symptomatic and rapid-growth HCHs located on the surface of the liver or adjacent to the gallbladder. Intraoperative ultrasonography is a useful adjunct for detecting additional liver lesions and offering more accurate targeting for RFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Gao et al 22 treated 36 hepatic hemangiomas with an average diameter of 10 ± 4 cm (5.0-21.5 cm) by RFA, the ablation time was 103 ± 27 min (40-160 min). Fan et al 23 reported that 27 patients with hepatic hemangiomas of 5.5 ± 2.0 cm in diameter were treated by laparoscopic RFA, in whom the average RFA time was 20.7 ± 11.9 min. In another report 24 the average RFA time was 60.5 ± 36.2 min (range 27-208 min).…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al 22 treated 36 hepatic hemangiomas with an average diameter of 10 ± 4 cm (5.0-21.5 cm) by RFA, the ablation time was 103 ± 27 min (40-160 min). Fan et al 23 reported that 27 patients with hepatic hemangiomas of 5.5 ± 2.0 cm in diameter were treated by laparoscopic RFA, in whom the average RFA time was 20.7 ± 11.9 min. In another report 24 the average RFA time was 60.5 ± 36.2 min (range 27-208 min).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone replacement therapy, in some degree, can treat hypothyroidism due to excessive resection of thyroid tissue.However, the efficacy of drug treatment is also controversial, andsome literature repored that levothyroxine had no obvious effects ininhibiting nodules10. Radiofrequency ablation (RFA), as a new minimally invasive treatment techonology developed in recent years, had been applied frequently in the treating abdominal cancer11, 12. With the maturation of this technology, RFA has been successfully applied in treating benign thyroid nodules or recurrent thyroid cancer in foreign countries13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic RFA, without resection, has been used to treat HH. Fan et al reported 27 patients treated with laparoscopic RFA with no recurrence at a mean of 21 months 17 . Still, the authors recommend that tumors larger than 10 cm be treated open with resection to prevent risk of massive bleeding.…”
Section: Discussionmentioning
confidence: 99%